Artificial Intelligence Tools Used in Editing and the Editing Profession - Rahime AKİKOL; Bahar ATMACA DEMİR (Etkileşim)
As a technological branch of art, film has historically collaborated with science to foster the development of new techniques. This collaboration has significantly influenced film production processes, especially the editing stage, which has continuously evolved with the introduction of advanced technologies. The trailer editing of director Luke Scott's 2016 movie Morgan, which would normally take 10-30 days, was completed in just one day with artificial intelligence technology used for the first time. Since then, artificial intelligence tools in film editing have changed the business practices of editors with automatic uses that reduce the tasks at hand. The aim of the study is to reveal how the profession of editing has transformed, perspectives on the future of the profession and professional concerns by explaining the editing practices that have changed with artificial intelligence through the experiences of Turkish editors. Artificial intelligence tools reduce the work time in the cinema and television sector and require the acquisition of different expertise. In the 2024 study, an in-depth interview was conducted with 11 editors with at least two years of experience in the broadcasting industry who made edits using different types of programs and different software, and the obtained data were categorized by descriptive analysis. Turkish editors indicated that artificial intelligence tools have facilitated their previously time-consuming and labour-demanding special effects, and that the works they did not do before are now included in their job descriptions. Although artificial intelligence creates a pessimistic perspective on the profession, the editors stated that the need for creative people will never end. This situation requires the editors to be good artificial intelligence users other than the editing program they use.